Optimalisasi Ibu Rumah Tangga dalam Peningkatan Ekonomi Keluarga melalui Pelatihan Teknik Shibori - Naila Najihah; Zainal Alim Adiwijaya; Mutoharoh Mutoharoh (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
Many housewives play a role in improving the family's economy by building a business. However, increasing business competition demands more creativity. Therefore, exploring creative business ideas needs to be done to provide business insight to housewives. This community service aims to optimize the role of housewives in improving family economic welfare through creative efforts. The target of this community service is a group of housewives who are active in family welfare improvement programs, namely the women of the Family Welfare Program (PKK) in hamlet (RW 1) Bangunharjo Village, Semarang. The service program is carried out in several stages. The program begins with field observations and business analysis according to partner need to provide creative business training. The result of this activity is to provide fabric coloring skills with the Shibori Technique to service participants. This activity produces ready-to-use products in the form of hijabs with unique motives that have high selling values. Thus, this provides business opportunities for housewives, so that they can optimize their role in improving the economic welfare of the family.